Synthesis and properties of cryptands with a thioether bridge and π-donors: silver(I) and copper(I)-complexes - Koschabek, René; Gleiter, Rolf; Rominger, Frank (European journal of inorganic chemistry, 2006)
The syntheses of seven bridgehead diazabicycloalkanes are reported. The bridges are represented by either a thioether chain and two 3-hexyne units (4 and 6-8), one selenoether chain and two 3-hexyne units (5), or one dithioether chain and two 4,4′-diethylbiphenyl units (9, 10). X-ray investigations reveal for 4-10 the in/in conformation at the bridgehead nitrogen atoms. Reactions with CuI triflate yield the endohedral CuI complexes of 4-6. Endohedral complexes of 6, 7, and 10 were isolated with silver triflate. X-ray investigations and spectroscopic studies on the metal complexes reveal interactions between the metal ion and the nitrogen-, chalcogen-, and π-units. In addition to the bicyclic systems 4-10 we synthesized the tripodal systems 28-33 in a one-pot reaction. In the cases of 28 and 33 we were able to isolate the corresponding AgI complexes. X-ray studies show an interaction between the metal ion and the nitrogen atom and one double bond of each of the three adjacent phenyl rings. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2006)
Published online: December 13, 2005
Gesehen am 23.10.2020